Effect Of Professional Competence And Skepticism On Audit Quality At The Papua Provincial Inspectorate - Z. D. Siahay, Adolf; C. Seralurin, Yohanes; Triayu Ervina, Melisa; Pattiasina, Victor (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to investigate the effect of professional competence and skepticism on audit quality at the Papua Provincial Inspectorate. The research population consists of 32 auditors working in the Papua Provincial Inspectorate Office with a minimum of 2 years of service, auditing experience, and a final education level of S1. Questionnaires were used to collect primary data from the respondents. The data was analyzed using multiple linear regression analysis in SPSS 26. The results indicate that both professional competence and skepticism have a significant positive effect on audit quality, as confirmed by the t-tests. The study contributes to the understanding of factors influencing audit quality and can serve as a reference for future research on the topic. Kata Kunci : competence, professional skepticism, audit quality